Hands-on Oracle Database 10g Express Edition for Windows - Bobrowski, Steven M. (Oracle Press., 2006)
Readers will learn to install the database on Windows and take full advantage of all of the powerful features. Tutorials and step-by-step guidelines throughout will equip you with the key concepts and hands-on experience necessary to get started using Oracle Database 10g Express Edition right away.